The Effect of the Functions of the Knowledge Management Maturity Triple Model on the Acquisition of Competitive Advantage Capabilities (Case Study: National Petrochemical Company) - Sayyed Mohammad Reza Davoodi; Mojgan Gharibi Marzankola; Mohammadreza Hamidizadeh; Valiullah Ali Mohammadi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study is conducted to investigate the effect of the functions of the knowledge management maturity triple model (Infosys model, general model, and KPMG model) on gaining competitive advantage capabilities in the National Petrochemical Company.Methodology: The present study contains 6 hypotheses (quantitative) and one question (qualitative). The statistical population is divided into two parts: the quantitative part includes 180 employees of the knowledge department of the National Petrochemical Company, and the qualitative part includes 10 experts from the company. The data collection tool is a questionnaire. SPSS23 and LISREL 8.80 statistical software were used to analyze the data.Findings: The results showed that the functions of the triple model of knowledge management maturity are effective in gaining competitive advantage capabilities in the National Petrochemical Company. The dimensions of the model functions (organizational processes, human resources, technology, and knowledge content) also affected the company's competitive advantage capabilities. Also, the National Petrochemical Company has higher adaptability among the triple maturity models, with the infusion model having an average of 3.62 and 72% and the KPMG and general models having an average of 3.3 and 25.2, respectively. They are in the second and third ranks.Originality/Value: Failure to pay attention to the functions of knowledge management maturity in the organization leads to the loss of intellectual capital, products, technologies, innovations, and creativity. Therefore, it is vital to study the effect of the functions of the triple model of knowledge management maturity (Infosys model, general model, and KPMG model) in gaining competitive advantage capabilities in the National Petrochemical Company.